Transcending the Technocratic Mentality through the Humanities - Sullivan, John (Religions, 2021)
Catholic education has a long tradition of engagement with the liberal arts and especially the humanities. The place of the humanities today in the curriculum is under threat for several reasons, one being the predominance of the technocratic mentality. This paper revisits (in three steps) the contested issue of the role of the humanities in education. First, I review arguments about the role of the humanities within education. Second, some of the defects of the technocratic mentality are pointed out. Third, a Christian lens for viewing the humanities is deployed. Here I propose that the humanities play a valuable role in nurturing the imagination, thereby contributing both to a capacity to transcend the technocratic outlook and to the development of the holistic and humanising education that is central to a Catholic worldview.